Empirical Decomposition and Forecast of Carbon Neutrality for High-End Equipment Manufacturing Industries - Lu, Hang; Elahi, Ehsan; Sun, Zhenya (Frontiers in Environmental Science, 2022)
Chinese government focuses on high-end equipment manufacturing industry to achieve a traget of carbon neutral. This study takes the China’s Bohai Rim as a case study. Firstly, we used the Tapio decoupling model to analyze the carbon emission status of the high-end equipment manufacturing industry in Bohai Rim. Secondly, LMDI was used to determine main factors of carbon emission. Similarly, Monte Carlo simulation predicted the time of carbon neutral. The results found that the relationship between carbon emission and the development of high-end equipment manufacturing industry is strong decoupling, but there is still a risk of "recoupling". The scale effect is the primary driving force for carbon emission reduction in the equipment manufacturing industry, followed by structural effect and carbon emission intensity effect. In the baseline scenario, low-carbon scenario, and technological breakthrough scenario, the carbon neutrality will be achieved in 2051, 2046 and 2042. The results of the study suggest that China should improve energy utilization efficiency and encourage green innovation.